Diversity and Distribution of Liverworts in Some Underexplored Areas of Manipur - Sahu, Vinay; Asthana, A K (Indian Forester, 2022)
Present study on liverworts diversity of some underexplored areas of Manipur has revealed the occurrence of 23 genera and 32 species of liverworts belonging to 17 families. Fourteen species have been reported for the first time from Manipur while three Indian endemic species (Cephalozia kashyapii Udar, Microlejeunea indica (Udar et U. S. Awasthi) Y. M. Wei. & R. L. Zhu and Notoschypus pandei Udar and Ad. Kumar) have also been identified from the explored sites.